Rebranding corporate identity of bustel Klebang Melaka / Shairah Sa’ari - Sa’ari, Shairah (2015)
This thesis presents the rebranding the corporate identity of Buster. This study carried out to attract more people and foreigner attention to visit the place to see distinctive of the Bustel uniqueness. Furthermore, the history of Bustel, it comes from the old buses that used as the public transport. They were not been thrown and recycled as the new bus branding. This study is to see the people's view and opinion throughout the new design and application to the Bustel.